Survey on Nutritional Status and Motor Skills of Lower-Class State Elementary School Students - Farhan Fauzan Damba Adiska; Febrita Paulina Heynoek; Abi Fajar Fathoni; Siti Nurrochmah (Sriwijaya Journal of Sport, 2024)
This research aims to examine and map the nutritional status and motor skills of lower grade elementary school students in Lowokwaru District, Malang City. This research is quantitative descriptive research using survey methods by means of interviews and observations. The sampling technique used was quota sampling with a total sample of 144 elementary school children aged 7-9 years, consisting of 72 boys and 72 girls. This research uses anthropometric instruments and the Test of Gross Motor Development-2 (TGMD-2). In analysing the data, this researcher used descriptive percentage data analysis techniques with the following results: (1) The nutritional status of lower grade elementary school children in Lowokwaru District, Malang City is predominantly in the normal category. (2) The level of motor skills of lower grade elementary school children in Lowokwaru District, Malang City is more dominant in the "average" category. Based on these results, it is recommended that teachers carry out measurements of nutritional status and motor skills in the context of learning evaluation. It is hoped that this evaluation can help improve the nutritional status of children and improve motor skills, especially basic movement skills, so that students can support their daily lives well.